Using training technology probes in bodystorming for physical training - Márquez Segura, E.; Turmo Vidal, L.; Parrilla Bel, L.; Waern, A. (Proceedings of the 6th International Conference on Movement and Computing, 2019)
A promising domain technology design for physical training is as assistive tangible and wearable tools to help people understand, access, and act on their movement senses. To design these tools in close relation to a targeted training practice, we propose an embodied design activity using Training Technology Probes (TTPs). These are pieces of technology with a simple interactivity augmenting and exteriorizing cues from those senses. Here, we explain how we used existing TTPs as design material to spur creativity in an embodied co-creation design workshop that happened as part of an ongoing technology-supported circus training course for children with motor difficulties. Our contribution is two-fold: We present a novel form of embodied ideation method using TTPs as design materials. We also present and characterize novel design concepts, elaborating on three that were implemented and deployed in the context of our circus training class. We discuss their relevance in several physical training domains.